2013
DOI: 10.1080/07373937.2013.802331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Emulsification of Fat on the Surface Tension of Protein Solutions and Surface Properties of the Resultant Spray-Dried Particles

Abstract: To examine the effect of protein adsorption on the fat-water interface on the surface composition of spray-dried particles, whey, hydrolyzed whey, and soy protein isolate emulsions were prepared at three different protein to fat ratios of 1:1, 1:5, and 1:10 and spray dried. Non-hydrolyzed whey protein isolate (WPI) and the more hydrolyzed whey protein solutions at 20.2% degree of hydrolysis (DH) had significantly lower surface tension values with fat than without fat. The correlation between the reduction of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
1
10
0
1
Order By: Relevance
“…Dislike extremely 1 maltodextrin depicted similar characteristics (Xu et al, 2013). In the present study, incorporation of a combination of GA with whey protein as wall material improved the barrier properties of the wall and this is because incorporation of polysaccharides in minor quantities will improve the encapsulation efficacy of whey protein (Anandharamakrishnan & Padma Ishwarya, 2015).…”
Section: Dislike Very Muchsupporting
confidence: 64%
“…Dislike extremely 1 maltodextrin depicted similar characteristics (Xu et al, 2013). In the present study, incorporation of a combination of GA with whey protein as wall material improved the barrier properties of the wall and this is because incorporation of polysaccharides in minor quantities will improve the encapsulation efficacy of whey protein (Anandharamakrishnan & Padma Ishwarya, 2015).…”
Section: Dislike Very Muchsupporting
confidence: 64%
“…Hydrolysis of phospholipids produces two main lysoforms, with the 1-acyl lysoform being predominant [ 44 ]. Higher levels of lipids reduce the surface tension of protein-containing solutions [ 45 ] and the electrical conductivity of aqueous solutions [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that WPI, which was used as a wall material in the encapsulation process, enhanced the coalescence of droplets (Abdel-Wahhab et al 2018). Moreover, the spherical shape of the particles indicated the presence of WPI in the wall of capsules (Eratte et al 2014;Xu et al 2013), and the negative zeta potential is also attributed to the negatively charged WPI in neutral pH which is mostly due to the carboxylate groups as the only charged functionalities present in WPI molecule (Eratte et al 2014). Generally, the surface properties and the particles size have a critical role in nanoparticles uptake by the mucus membranes and the size of 50-300 nm is the preferred size for uptake (Roger et al 2010) and affect the pharmacokinetics, tissue distribution and clearance of nanoparticles (Sadat et al 2016).…”
Section: Discussionmentioning
confidence: 99%